Length-weight relationship of Johnieops sina (Cuvier, 1830) off Cochin, south-west coast of India - Venugopal, N.; Pillai, N. G. K.; Prakasan, D. (Indian Journal of Fisheries, 2013)
Length-weight relationship of Johnieops sina was estimated from 392 males and 487 females in the length range of 102-208 mm (TL), collected from fish landings at Cochin and Munambam fisheries harbours as well as Vypin fish landing centre in Kerala, on the south-west coast of India during the period from January 2008 to June 2010. The length-weight relationship equations were derived as W= 0.000074956 L 2.6260 for males and W = 0.0000426 L 2.7393 for females. Analysis of covariance showed that there is no significant difference between sexes (p>0.05). Hence, common length-weight relationship using pooled data of the two sexes was derived as W=0.00005854 L 2.6753. Results of the Student’s t-test indicated significant deviation of ‘b’ from ‘3,’ tending towards negative allometric growth (p<.0.05).